Strumienie transferu i retransferu dochodów pomiędzy rolnictwem a gospodarką narodową w procesie integracji Polski z Unią Europejską - Kułyk, Piotr (Flows of Incomes Transfer and Retransfer Between Agriculture and National Economy in the Integration Process of Poland with the European Union, 2005)
The article presents considerations of a support of agricultural regime in the EU and Poland and retransfer of incomes in this regime. Applied stimulus of fiscal policy has great importance of creating of target model of transformation. The article consists of two parts. In the first part the most important indicators according to OECD's methodology from the angle of created food economy model and flow of financial transfer are discussed. The second part presents evaluation of support regime in the EU and Poland and its influence on economic situation of particulars groups of economic participants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 532-537